2023
DOI: 10.1002/adfm.202309807
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter‐Mediated Plasticity in 2D Perovskite Memristor for Reinforcement Learning

Yan Wang,
Shidong Chen,
Xiaohan Cheng
et al.

Abstract: The neuromorphic computing architecture is a promising artificial intelligence for implementing hierarchical processing, in‐memory computing, event‐driven operation and functional specialization in computing systems. However, current investigations mainly focus on unisensory processing without objective experience which is contrary to the flexible sensory learning capability in the human brain that can sense and process information according to the ever‐changing environment. For example, a dominant paradigm fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In addition, it is noteworthy that the quasi-2D BA 0.15 FA 0.85 PbI 3 perovskite occupies an intermediary position between pure 2D and 3D perovskites, combining the advantages of both structures. Furthermore, when compared to some kinds of materials including matel oxides, polymers, pure 2D perovskites, and pure 3D perovskites, the quasi-2D perovskite displays superior repeatability and enhanced stability. In comparison to 3D perovskite configurations, the quasi-2D perovskite demonstrates a lower current flow and reduced power consumption. Compared with polymer and organic materials, the quasi-2D perovskites have a better endurance ability by a large margin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is noteworthy that the quasi-2D BA 0.15 FA 0.85 PbI 3 perovskite occupies an intermediary position between pure 2D and 3D perovskites, combining the advantages of both structures. Furthermore, when compared to some kinds of materials including matel oxides, polymers, pure 2D perovskites, and pure 3D perovskites, the quasi-2D perovskite displays superior repeatability and enhanced stability. In comparison to 3D perovskite configurations, the quasi-2D perovskite demonstrates a lower current flow and reduced power consumption. Compared with polymer and organic materials, the quasi-2D perovskites have a better endurance ability by a large margin.…”
Section: Resultsmentioning
confidence: 99%
“…The low energy consumption of 12.4 fJ ensures high power efficiency and in-sensor computing with a synapse showcasing the feasibility of 2D perovskite neuromorphic devices with enhanced biological plausibility in the post-Moore era. 26 Li et al introduce a hybrid 2D/3D perovskite heterostructure, achieved by depositing n-butylammonium iodide on the perovskite surface, enhancing resistive switching memory devices with improved performance, offering new possibilities for high-performance perovskitebased memory devices in next-generation technology. 27 Zhang et al explore 0D perovskite, 2D perovskite, and 1D perovskite films in memristors, demonstrating their exceptional stability, superior ON/OFF ratios, and dimensionality-dependent effects on resistive switching behaviors, while also simulating biological synapse plasticity and successfully emulating associative learning behavior.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the near-sensor visual system, the in-sensor visual system has been systematically researched due to the proposal of a wide variety of photo-induced resistive materials [147][148][149][150][151][152]. This means that neuromorphic devices can be modulated by an optical spike being directly dropped into the procedure of electric spike converting.…”
Section: Flexible In-sensor Visual Systemmentioning
confidence: 99%
“…Memristors have the potential to overcome the limitations of Von Neumann systems in terms of their program operation modes, enabling them to efficiently process and store vast amounts of data. Memristors have a simple sandwich structure similar to that of biological synapses. Biological research has shown that the human brain is made up of about 10 15 synapses, essentially making it a natural supercomputer that combines low-power consumption with high performance. Brain-like biomimetic memristors are an important direction for future artificial intelligence computing applications, and constructing memristor devices compatible with the current computing architectures and implementing neuromorphic computing is a promising approach.…”
Section: Introductionmentioning
confidence: 99%